(untitled) (Universa Medicina, 2015)
BACKGROUND Approximately 10-27% of the population aged >65 years suffers from frailty. The percentage increases with age so that the prevalence of frailty in the population aged >85 years reaches 45%. The objective of this study was to determine the relationship between frailty and quality of life (QOL) in nursing home elderly. METHODS This was a cross-sectional study of 138 subjects aged >60 years who were recruited from 4 nursing homes in West Jakarta. Participants with frailty status were evaluated by the Survey of Health, Ageing and Retirement in Europe (SHARE) instrument and QOL was evaluated by the WHOQOL-BREF questionnaire. One-way ANOVA and chi-square tests were used to find relations between the frailty syndrome and QOL. RESULTS The percentages of respondents with pre-frail, frail, and non-frail status were 30.4%, 52.2%, and 17.4%, respectively. A decline in QOL scores of pre-frail and frail respondents was found for almost all QOL domains (physical, psychological and environment domains), except social relationships. The subdomains most influenced were “energy and fatigue” in the physical health domain, “thinking, learning, memory and concentration” in psychological health, and “opportunities for acquiring new information and skills” in the environment domain. CONCLUSIONS More than half of the nursing home elderly were frail and one-third were pre-frail. The main factor of frailty was weakness. The frailty syndrome in the elderly has a negative impact on QOL, especially in the physical health, psychological and environment domains in nursing home elderly.